Credit Risk in Lending to Small and Medium sized Enterprises- The case of Vietinbank, Hoan Kiem Branch,Graduation Thesis - Nguyen Thi Viet Ha,Ngo Tung Anh,Vu Thanh Ha
Credit Risk in Lending to Small and Medium sized Enterprises- The case of Vietinbank, Hoan Kiem Branch : Graduation Thesis / Nguyen Thi Viet Ha; Ngo Tung Anh, Vu Thanh Ha co-suppervisor .- H. : Banking Academy , 2012 .- 41 p. ; 28 cm